Introduction to statistical mediation analysis - MacKinnon, David Peter (Multivariate application series, 2008)
This volume introduces the statistical, methodological, and conceptual aspects of mediation analysis. Applications from health, social, and developmental psychology, sociology, communication, exercise science, and epidemiology are emphasized throughout.